2019
DOI: 10.3390/nu11040784
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Patterns of Grain-Based Foods among Adults in Canada: Evidence from Canadian Community Health Survey—Nutrition 2015

Abstract: In this study, we used the Canadian Community Health Survey-Nutrition (CCHS) 2015 data to examine the consumption patterns of grain-based foods (GBFs) for Canadian adults. We used a k-mean cluster analysis based on the contribution of 21 grain-based foods to total energy intake of adults in Canada to find the dietary patterns of GBFs. Cluster analyses rendered seven dietary patterns including: ‘other bread’, ‘cake and cookies’, ‘pasta’, ‘rice’, ‘mixed’, ‘white bread’, and finally ‘whole wheat and whole-grain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In this study, the major sources of dietary riboflavin were vegetables (26%) and milk and alternatives (25%), followed by meat and alternatives (16%) and grains (14%). The contribution of grains was slightly lower than that reported by a study of the contribution of nutrients from grain-based foods from the 2015 CCHS, in which grain-based foods contributed 19% of riboflavin intake in Canadians; however, the results included both males and females, and children (≥2 y; n = 19,797) ( 19 ). It is not surprising that 25% of dietary riboflavin intake was from milk and alternative sources.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In this study, the major sources of dietary riboflavin were vegetables (26%) and milk and alternatives (25%), followed by meat and alternatives (16%) and grains (14%). The contribution of grains was slightly lower than that reported by a study of the contribution of nutrients from grain-based foods from the 2015 CCHS, in which grain-based foods contributed 19% of riboflavin intake in Canadians; however, the results included both males and females, and children (≥2 y; n = 19,797) ( 19 ). It is not surprising that 25% of dietary riboflavin intake was from milk and alternative sources.…”
Section: Discussioncontrasting
confidence: 62%
“…This survey is now >15 y old. Two recent studies in Canada on the contribution of dairy products and grains to nutrient intake reported that milk and alternatives contributed 24% of total riboflavin intake in adults, and that grain products contributed 19% of total riboflavin intake in participants aged ≥2 y, using data collected from the 2015 CCHS ( 18 , 19 ); the contribution of other food sources to riboflavin intake in Canada remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason behind considering these categories was the recommendations made by the CFG and the United States Department of Agriculture, suggesting that at least half of the grain intakes should be whole grains [3,23]. Following these recommendations and the previous studies showing that refined grains could contribute to the intakes of some key nutrients for both children and adults in Canada [24,25], a pattern of whole-grain consumption (i.e., the balanced intake of grains) was defined where the share of whole grain intakes was between 40% to 60% of the total daily intakes of grain. The other patterns of whole grain intakes in this study were defined around the balanced pattern of consumption…”
Section: Methodsmentioning
confidence: 99%
“…Among the cereal‐based products, bread represents the most commonly consumed category in several countries in Europe and North America (Hosseini et al., 2019; Laskowski, Gorska‐Warsewicz, Rejman, Czeczotko, & Zwolinska, 2019; Papanikolaou & Fulgoni, 2017). Cookies, cakes, and pasta are also frequently consumed (Hosseini et al., 2019), though none of these items are traditional food uses for proso millet. Wheat is the most suitable raw material for the production of pasta and baked goods, due to the unique viscoelastic properties of its gluten proteins.…”
Section: Processing: Part Of the Yellow Cluster But Linked To All Otmentioning
confidence: 99%